FAKTOR YANG MEMPENGARUHI PENGGUNAAN HP BLACKBERRY OLEH REMAJA DIKELURAHAN PARAK LAWEH KECAMATAN LUBUK BEGALUNG PADANG - Putra, Deden Tri Sang; Mellyarti, Mellyarti; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Teens are growing teenagers who can adapt to the times that more and more advanced. Essentially the current era of globalization has made significant changes have occurred and moral degradation and social culture that tends to deviant behavior pattern. Social behavior is rejected by the group as a result of the influence of self-concept that is not true in adolescents and the influence of foreign cultures that are not controlled by some teenagers. Outside cultural influences swallowed whole by teenagers without known far beyond the cultural values without responsibility. Bright spots that human life begins at the simplicity of it has been beneficial to facilitate all aspects of life called technology. World of information at this time seemed not be separated from technology. Public consumption will technology make the world more and more sophisticated technology. Communication is used to take a long time in its delivery, now with technology being so close to everything and without distance study aimed to medeskripsikan: internal influence factors and the use of Hp BlackBerry exksternal the social development of adolescents In this study, researchers analyzed existing indicators in the sub-indicator indicators, namely: a) the internal influence; (1) Human needs (teens) (2) self-concept, and b) External influences: (1) parental influence (2) The effect of school (3) the influence of peers